Settlement of Bad Loans Through Auction Execution of Customer Rights at Bank Syariah Indonesia: english - Erwin Putra Pratama; Markoni; Joko Widarto; Horadin Saragih (Unram Law Review, 2024)
Bank Syariah Indonesia (BSI) is an Islamic bank institution that provides financing to customers. BSI KCP Tangerang City, one of the sub-branch offices, needs help financing the wrong customers. The bank analyzes financing and applies collateral as collateral for customer financing. This research has a problem formulation: how to resolve lousy credit through auction execution of mortgage rights. This research used the normative juridical approach through interviews with data sources, laws, and literature studies. The results of this study indicate that BSI KCP Tangerang City applies an auction for a bad debt if the customer's financing has a bad status and is reluctant to pay his debts under Bank Indonesia Regulation No. 14/15/PB/2012 concerning Asset Quality Assessment of Commercial Banks. The bank considers the relief efforts of restructuring negotiations, such as rescheduling, reconditioning, and restructuring, given time, to the sale of collateral. The implementation and procedures of the auction are submitted to the KPKNL by the Minister of Finance Regulation Number 213 / PMK.06 / 2020 concerning Guidelines for the Implementation of Auctions. The bank conducts collateral credietverband; the sale proceeds are handed over to the customer after deducting KPKNL fees. The bank needs to review the application of the prudential principle, 5C, 7P, and 3R credit analysis to minimize lousy credit. Customers are advised to be able to reconsider the feasibility of their ability before applying for credit from the bank.